1973
DOI: 10.1103/physrevlett.31.66
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino-Induced Muons Deep Underground

Abstract: Dividing both sides of (14) by {o P + o A ) E , it is straight forward to show ( E r l/2 ]We define the unboundedness of the total cross sections as lim {o P J) B = «>.Hence if (o>) and (cr A > are both unbounded the rhs of (15) is zero which is the desired result [Eq.(1)]. Equation (14) shows that the same result holds if only one of the total cross sections is assumed to be unbounded; it then follows that the other cross section must be unbounded, too. From Eq. (1) or (10) it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The first atmospheric neutrino experiments observed these muons in the 1960s (Achar et al, 1965a(Achar et al, , 1965bReines et al, 1965Reines et al, , 1971Krishnaswamy et al, 1971;Bergeson, Cassiday, and Hendricks, 1973;Crouch et al, 1978). Then in the late 1970s a large-scale experiment using liquid scintillators was begun at Baksan (Boliev et al, 1981).…”
Section: Upward Through-going Muonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first atmospheric neutrino experiments observed these muons in the 1960s (Achar et al, 1965a(Achar et al, , 1965bReines et al, 1965Reines et al, , 1971Krishnaswamy et al, 1971;Bergeson, Cassiday, and Hendricks, 1973;Crouch et al, 1978). Then in the late 1970s a large-scale experiment using liquid scintillators was begun at Baksan (Boliev et al, 1981).…”
Section: Upward Through-going Muonsmentioning
confidence: 99%
“…Another experiment was begun during the late 1960s (Bergeson, Cassiday, and Hendricks, 1973). Since this detector was located at a relatively shallow depth (about 1500 mwe), horizontally going particles, as well as the downward going particles, were dominated by cosmicray muons, and only upward going muons were selected as neutrino events.…”
Section: Introduction and Historymentioning
confidence: 99%
“…The anomalies in muon depth-intensity which they reported in 1967-71 provided one of the initial motivations to build underwater detectors. In 1973, the Utah group reported also first results on neutrinos [Bergeson 1973]. Combining their energy spectra with those of the KGF group they concluded that the spectrum is consistent with a linear growth of the neutrino cross-section up to high energies and that the W-boson mass has to be large.…”
Section: From First Concepts To the Detection Of Atmospheric Neutrinosmentioning
confidence: 94%
“…This would be the case if the total neutrino-nucleon cross section rose linearly with laboratory neutrino energy. The rough prediction was equal numbers of events per factor of 10 in incident neutrino energy (16). And the energy resolution of Jack's detector extended up to hundreds of GeV.…”
Section: Partonsmentioning
confidence: 99%